The Effectiveness of Learning to Write Expository Text Using the Think Talk Write Model Assisted by Animation Video Media Based on the Level of Creative ThinkingFor Class VIII Students - Hidayah, Nasik; Wagiran Wagiran; Haryadi Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Writing expository texts is one of the skills that class VIII junior hight school students must have. Expository text aims to explain something to broaden the mind, insight or knowledge of the reader. Appropriate learning is using the think talk write learning model assisted by animated video media based on students' level of creative thinking. This research aims to examine the effectiveness of the think talk write learning model in teaching expository text material, based on students' level of creative thinking. This research method uses quasi-experiment, with purposive sampling technique for sampling. Instrument data analysis involves validity and reliability tests, while normality and homogeneity tests are used for sample testing. Final data analysis was carried out using a paired sample t-test with the SPSS 24 program. The research results showed that the think talk write learning model assisted by animated video media was effectively applied in learning to write expository texts for class VIII students, especially for students with a creative thinking level. tall one. This model is more effective for students with a high level of creative thinking compared to students who have a medium or low level of thinking. This research is useful for developing research in the field of education, increasing knowledge about writing expository texts, and providing insight into effective learning models.